Pengaruh Pembelajaran Berbasis Proyek Pembuatan Terarium (Ekosistem Mini) Terhadap Kemampuan Berpikir Kritis Peserta Didik Pada Materi Ekosistem Kelas X Mas Al-Washliyah 26 Tinokkah - Safitri, Bella; Ulfa, Syarifah Widya (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to assess the effect of project-based learning on making terrariums (mini ecosystems) on students’ critical thinking skills in ecosystem material for grade X. This study uses a quantitative approach with a quasi-experimental design method with a pretest-posttest control group design type. The research subjects were grade X students of MAS Al-Washliyah 26 Tinokkah consisting of 25 people in the experimental class and 23 people in the control class. The research instrument was an essay test consisting of 5 questions to measure critical thinking skills that had been tested for validity and reliability. Data were analyzed using descriptive statistics, normality tests, homogeneity tests, and independent sample t-tests with the help of the SPSS program version 26.0. The results showed that the average posttest score of the experimental class (81.60) was higher than that of the control class (60.43). The t-test proved a significant difference between the two classes (p < 0.05), thus it can be concluded that the terrarium-making project-based learning model has a positive effect on improving the critical thinking skills of class X students at MAS Al-Washliyah 26 Tinokkah. This finding proves that the Project Based Learning (PJBL) model has a positive effect on improving the critical thinking skills of class X students at MAS Al-Washliyah 26 Tinokkah.